Setting priorities for mental health research in Brazil - Gregório, Guilherme [UNIFESP] (2012)
BACKGROUND: The main aim of this study is to review the agenda for research priorities of mental health in Brazil. METHODOLOGY: The first step was to gather 28 experts (22 researchers, five policy makers, and the coordinator) representing all mental health fields from different geographical areas of the country. Participants were asked to list what they considered to be the most relevant mental health research questions for the country to address in the next 10 years. Seventeen participants answered this question; after redundancies were excluded, a total of 110 responses were collected. As the second step, participants were asked to rank which questions were the 35 most significant. The final step was to score 15 items for each of the 35 selected questions to determine whether it would be a) answerable, b) effective, c) deliverable, d) equitable, and e) effective at reducing the burden of mental health. The ten highest ranked questions were then selected. RESULTS: There were four questions addressing primary care with respect to a) the effectiveness of interventions, b) matrix support, c) comparisons of different models of stepped care, and d) interventions to enhance identification and treatment of common mental disorders at the Family Health Program. The other questions were related to the evaluation of mental health services for adults and children/adolescents to clarify barriers to treatment in primary care, drug addiction, and severe mental disorders; to investigate the cost-benefit relationship of anti-psychotics; to design interventions to decrease alcohol consumption; and to apply new technologies (telemedicine) for education and supervision of non-specialists. CONCLUSION: This priority-setting research exercise highlighted a need for implementing investments at the primary-care level, particularly in the family health program; the urgent need to evaluate services; and policies to improve equity by increasing accessibility to services and testing interventions to reduce barriers for seeking mental health treatment.